The Effect of Coffee Consumption on the Severity of Acne Vulgaris in Students of Universitas Prima Indonesia - Jaqueline Francetta; Herlin Novita Pane; Muhammad Chairul (International Journal Labs, 2025)
Acne vulgaris is a common skin disorder in adolescents and young adults, characterized by the presence of non-inflammatory and inflammatory lesions on the pilosebacebase unit. This condition is influenced by various factors such as hormonal, genetic, stress, and diet. Coffee as a caffeinated beverage is widely consumed by college students, so it is interesting to research its relationship with the severity of acne vulgaris. Objective: This study aims to analyze the effect of coffee consumption on the severity of acne vulgaris in students of the Faculty of Medicine, Universitas Prima Indonesia class of 2022–2024. Methods: This study is an analytical observational study with a cross-sectional approach. The sample consisted of 30 respondents who were selected using purposive sampling techniques according to inclusion and exclusion criteria. Data collection was carried out through the Food Frequency Questionnaire (FFQ) questionnaire to assess coffee consumption and the Global Acne Grading System (GAGS) to assess the severity of acne vulgaris. Data analysis was carried out using the Chi-Square test with a significance level of 0.05. Results: The majority of respondents were female (70%) and had a moderate level of coffee consumption (56.7%). The most severe acne vulgaris was found in the mild category (60%). The bivariate test showed a value of p = 0.057 (>0.05), which indicates that there is no significant relationship between coffee consumption and the severity of acne vulgaris. Conclusion: Coffee consumption was not significantly related to the severity of acne vulgaris in students of the Faculty of Medicine, Universitas Prima Indonesia. Other factors such as the type of coffee, drink mix, diet, stress, and genetic predisposition may also affect the onset of acne vulgaris.